Recent Advances in Radical Reactions of Vinyl Triflates and Their Derivatives - Kawamoto, Takuji; Kamimura, Akio (Synthesis, 2022)
Vinyl triflates are valuable precursors for vinyl cations and vinyl carbenes and serve as electrophiles in transition-metal-catalyzed cross-coupling reactions. However, the scope of radical reactions involving vinyl triflates has been very limited until recently. In this short review, we summarize the recent development on two categories of radical reactions involving vinyl triflates, i.e., radical trifluoromethylations and radical non-trifluoromethylations of vinyl triflates.1 I ntroduction to Vinyl Triflates2 Earlier Work on Radical Reactions of Vinyl Triflates3 Radical Trifluoromethylations of Vinyl Triflates and Their Derivatives4 Radical Non-Trifluoromethylation of Vinyl Triflates5 Conclusions and Outlook
Keywords: radical reactions; trifluoromethylations; vinyl triflates; ketones; alkynes; alkenes